Teacher Assessment Profile of Student Collaboration Skillin Science and Biology Learning - Nurul Hidayati; Bowo Sugiharto; Maridi Maridi (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2020)
Education is a means of creating a generation that is capable of coping with 21st- century challenges. The generation of the 21st century must master various skills that support high-order thinking. One of those skills is collaboration skill. This study aims to analyze the assessment profile of collaboration skills performed by Junior High School science teachers and Senior High School biology teachers in Solo Raya. This research employed a survey method involving 125 samples, comprising 49 Junior High School science teachers and 76 Senior High School biology teachers in Solo Raya. Collecting data use an instrument which was a development of the collaboration skill aspect based on NEA and P21. The data analyzed using the Rasch model. It was found that the items of the questionnaire in each construct had varied discriminatory powers showing that the instrument had a measuring ability. The overall analysis result of the respondents’ opinions was above the mean logit score (+0.00 logit) which proved that the teachers had implemented the assessment of collaboration skills. The results of the univariate analysis based on the respondents’ characteristics concluded that Junior High School science teachers (39.2%) had assessed the students' collaboration skills